1997
DOI: 10.1007/s003300050194
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of percutaneous ethanol injection therapy for hepatocellular carcinoma in cirrhosis: a European experience

Abstract: The objective of our work was to evaluate the long-term results of percutaneous ethanol injection (PEI) for the treatment of hepatocellular carcinoma (HCC) in patients with liver cirrhosis. A total of 184 cirrhotic patients with HCC underwent PEI as the only anticancer treatment over an 8-year period. Patients were followed after therapy by means of clinical examinations, laboratory tests, and US and CT studies performed at regular time intervals. Survival rates were determined according to the Kaplan-Meier me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(90 citation statements)
references
References 45 publications
(77 reference statements)
5
81
0
4
Order By: Relevance
“…For the referent strategy, CT is performed if AFP level is greater than 200 ng/mL. [34][35][36][37][38] In the U/S screening strategy, patients undergo CT if U/S suggests a mass. Screening with U/S and AFP level are performed in parallel with the U/S plus AFP strategy.…”
Section: Screening Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the referent strategy, CT is performed if AFP level is greater than 200 ng/mL. [34][35][36][37][38] In the U/S screening strategy, patients undergo CT if U/S suggests a mass. Screening with U/S and AFP level are performed in parallel with the U/S plus AFP strategy.…”
Section: Screening Strategiesmentioning
confidence: 99%
“…Screening with U/S and AFP level are performed in parallel with the U/S plus AFP strategy. If AFP level is greater than 200 ng/mL or U/S detects a suspicious mass, then patients undergo CT. [34][35][36][37][38] Patients undergo an abdominal computed tomographic scan for the CT strategy. Biopsies are performed on masses found by CT for any of these strategies.…”
Section: Screening Strategiesmentioning
confidence: 99%
“…Resection and transplantation achieve the best outcomes in well-selected candidates (5-year survival 60%-70%) [13][14][15][16] , and compete as the first option from an intention-to-treat perspective [17] . Percutaneous treatments provide good results (5-year survival 40%-50%) [11,18] , but have not been able to achieve response rates and outcomes comparable to surgical treatments [11,12] . Liver transplantation has been suggested as the best treatment for patients with one tumor and decompensated cirrhosis or multicentric small tumors [19] .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this modality does carry the risk of disseminating the tumor by facilitating the passage of malignant cells into the blood stream, but that was opposed by other authors, who consider that because ethanol diffuse along the needle tract, its cytotoxic effect and small vessel thrombosis minimize the risk seeding. 23 The most common side effect of alcohol injection is leakage of alcohol onto the surface of the liver and into the abdominal cavity, thereby causing pain and fever. It is important that the location of the tumor relative to the adjacent blood vessels and bile ducts is clearly identified.…”
Section: Complicationsmentioning
confidence: 99%
“…23 The endpoint of local ablation is complete tumor necrosis with a margin of tissue. Of the methods of ablation, PEI and RFA are commonly performed and are effective as well.…”
Section: Comparison Of Pei To Other Treatmentmentioning
confidence: 99%